Enhancing conceptual understanding in physics: An innovative interactive multimedia learning environment for teaching Newtonian gravity - Echantoufi, Noureddine; Khattabi, Khalid El; Lamrabet, Mohammed; Fakhar, Hamza; Ajana, Lotfi (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of an Interactive Multimedia Learning Environment (IMLE) on students’ comprehension of Newtonian gravity. A quasi-experimental design compared an IMLE-supported experimental group with a traditionally taught control group. Conceptual learning was assessed using the Newtonian Gravity Concept Inventory (NGCI), while motivation was measured via the Science Motivation Questionnaire II (SMQ II). Results showed significantly greater improvement in students’ conceptual understanding of Newton’s law of gravitation in the experimental group exposed to an IMLE, compared to the control group receiving traditional instruction. Paired samples t-tests indicated significant gains in NGCI scores within the experimental group (p<0.001). Independent t-tests confirmed that these gains were significantly higher than those of the control group (p<0.001). Additionally, ANCOVA showed no significant effect of gender on posttest performance, indicating that the benefits of IMLE were consistent across genders. Pearson correlation analyses highlighted significant positive relationships between NGCI posttest scores and all dimensions of science motivation, particularly grade motivation (r=0.886) and self-efficacy (r=0.857). These findings suggest that IMLE not only enhances conceptual learning but also positively influences student motivation in science education. Furthermore, they underscore the educational potential of incorporating interactive multimedia learning environments in the instruction of complex and abstract scientific concepts.